The impact of the COVID-19 pandemic on neurofibromatosis clinical care and research - Radtke, Heather B. (Orphanet J Rare Dis, 2021)
PURPOSE: The coronavirus disease 2019 (COVID-19) pandemic has had unprecedented impact on the provision of medical care for genetic disorders. The purpose of this study was to assess the effects of the pandemic on neurofibromatosis (NF) care and research. METHODS: Sixty-three United States NF clinics were surveyed to identify the impact of the pandemic on clinician role, patient volume, continuity of guideline-driven surveillance, research protocols, and use of (and satisfaction with) telehealth for the delivery of NF care. RESULTS: Fifty-two clinic directors or their representatives completed the survey (83% response rate). About 2/3 of the clinics reported a greater than 50% decrease in the number of available patient appointments, and modified clinical surveillance and research protocols. Fifty-one clinics (98%) newly instituted telehealth during the pandemic. Barriers to telehealth prior to the pandemic were insurance reimbursement concerns and lack of infrastructure. Since telehealth was initiated, high provider satisfaction was reported with ease of use. The most common area of concern was related to inability to perform a physical examination. CONCLUSION: Results show marked impacts on NF care and research since the beginning of the pandemic, with potential long-term changes related to the introduction (or adoption) of telehealth for clinical care.